The Matthew Effect Possibly Caused by Light Tax Burden: An Economic Analysis Based on the Land and Population Tax Systems During the "Reign of Wen and Jing" in the Western Han Dynasty (Journal of economic and management development research, 2025)
Traditional historical views usually regard the "one-thirtieth tax rate" policy of light corvée and low taxes during the "Reign of Wen and Jing" as a model of benevolent governance. However, this paper aims to re-examine the long-term socio-economic impacts of this policy from the perspectives of institutional economics and fiscal sociology. The study finds that the "one-thirtieth tax rate", as a low-tax policy levied based on land area, led to insufficient national fiscal revenue due to the imbalance between collection costs and benefits. To make up for the deficit, the imperial court turned to strengthen and rely on a fiscal extraction model centered on the poll tax (including Suanfu and Koufu). Under the social condition of extremely uneven land ownership, this dual tax structure of "light land tax and heavy poll tax" produced a significant "Matthew Effect": the large landlord class enjoyed huge dividends from the low land tax but only bore a slight poll tax burden that was mismatched with their wealth; while self-cultivating farmers and tenant farmers, although benefiting from the nominal light land tax, found it difficult for their limited land output to offset the heavy and fixed poll tax pressure. The regressive nature of this tax burden, under the impact of natural disasters and man-made calamities, forced small peasant families into a vicious cycle of "selling land to pay taxes - land annexation - losing land and becoming exiles". This eventually accelerated the concentration of social wealth in the hands of powerful landlords and created a large number of exiles who were out of the state's household registration control, laying the groundwork for the social crisis in the mid-Western Han Dynasty. This paper argues that the merit of a tax policy should not be judged merely by the level of its nominal tax rate, but more by examining its structural position in the entire fiscal system, its collection efficiency, and its ultimate social distribution effect.
Keywords: Reign of Wen and Jing; one-thirtieth tax rate; poll tax; Matthew Effect; land annexation; fiscal structure